Spinal Wnt5a plays a key role in apinal dendritic spine remodeling in neuropathic and inflammatory pain models and in the proalgesic effects of peripheral Wnt3a - Simonetti, Manuela; Kuner, Rohini (The journal of neuroscience, 2020)
Wnt signaling represents a highly versatile signaling system, which plays critical roles in developmental morphogenesis as well as synaptic physiology in adult life and is implicated in a variety of neural disorders. Recently, we demonstrated that Wnt3a is able to recruit multiple noncanonical signaling pathways to alter peripheral sensory neuron function in a nociceptive modality-specific manner. Furthermore, several studies recently reported an important role for Wnt5a acting via canonical and noncanonical signaling in spinal processing of nociception in a number of pathologic pain disorders. Here, using diverse molecular, genetic, and behavioral approaches in mouse models of pain in vivo, we report a novel role for Wnt5a signaling in nociceptive modulation at the structural level. In models of chronic pain, using male and female mice, we found that Wnt5a is released spinally from peripheral sensory neurons, where it recruits the tyrosine kinase receptors Ror2 and Ryk to modulate dendritic spine rearrangement. Blocking the Wnt5a-Ryk/Ror2 axis in spinal dorsal horn neurons prevented activity-dependent dendritic spine remodeling and significantly reduced mechanical hypersensitivity induced by peripheral injury as well as inflammation. Moreover, we observed that peripheral Wnt3a signaling triggers the release of Wnt5a in the spinal cord, and inhibition of spinal Wnt5a signaling attenuates the functional impact of peripheral Wnt3a on nociceptive sensitivity. In conclusion, this study reports a novel role for the Wnt signaling axis in coordinating peripheral and spinal sensitization and shows that targeting Wnt5a-Ryk/ROR2 signaling alleviates both structural and functional mechanisms of nociceptive hypersensitivity in models of chronic pain in vivo. - SIGNIFICANCE STATEMENT There is a major need to elucidate molecular mechanisms underlying chronic pain disorders to develop novel therapeutic approaches. Wnt signaling represents a highly versatile signaling system, which plays critical roles during development and adult physiology, and it was implicated in several diseases, including chronic pain conditions. Using mouse models, our study identifies a novel role for Wnt5a signaling in nociceptive modulation at the spinal cord level. We observed that Wnt5a recruits Ror2 and Ryk receptors to enhance dendritic spine density, leading to nociceptive sensitization. Blocking the Wnt5a-Ryk/Ror2 interaction in the spinal dorsal horn prevented spine remodeling and significantly reduced inflammatory and neuropathic hypersensitivity. These findings provide proof-of-concept for targeting spinal Wnt signaling for alleviating nociceptive hypersensitivity in vivo.
Gesehen am 16.10.2020